Numerical simulation of reactive flow in non-equilibrium behind a strong shock wave during re-entry into earth's atmosphere. (7th April 2014) - Allouche, R.; Haoui, R.; Renane, R.
<x content-type="archive" xml:space="preserve">Abstract</x> In this paper, we study the phenomena of thermo-chemical imbalance in a reactive mono-dimensional flow composed of a mixture of (79% nitrogen N2 and 21% oxygen O2). We are interested in modeling the physicochemical process that may be encountered in hypersonic flows, as vibrational excitation, dissociation and ionization, also the formation of chemical species to higher temperatures behind a detached strong shock. We put a special emphasis on vibrational relaxation model of CVD coupling. At these high temperatures, collisions electrons-atoms become very effective, taking in account the radiation that requires knowledge and modeling of all physicochemical processes (collisional and radiative). The mathematical model of flows at the atmospheric reentry is governed by Euler stationary equations coupled with the chemical kinetics and the radiative transfer equations. Our computational code is based on the finite differences method that used to discretize and resolve the obtained numerical model, where an appropriate mesh is selected in the relaxation zone in order to determine the flow parameters at each grid position